2019
DOI: 10.1021/acs.orglett.9b03645
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to Allenylphosphine Oxides via a Metal Free Coupling of Propargylic Substrates with P(O)H Compounds

Abstract: A direct and convenient approach for the coupling of propargylic substrates with diphenylphosphine oxide in the presence of Tf 2 O and 2,6-lutidine has been developed. The method provides a general approach for the construction of attractive allenylphosphoryl skeletons with high atom and step economy under metal free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In 2019, employing alkynes with various leaving groups, the Chang group demonstrated that propargylic compounds 67a could be also used as nucleophile partners in the presence of electrophilic P-species to generate allenylphosphine oxides 67b (Scheme 67). 114 In this protocol, diverse leaving groups such as OAc, OTs, OMs, OP(O)(OPh)2, and halides can be installed on the alkyne substrates to afford the allenylphosphine oxides. Both alkyl and aryl substituents on R 1 -position of the alkynes were tolerated to give the target products 67c, 67d with high yields of 87% and 74%, respectively.…”
Section: Scheme 65 Proposed Mechanism For Hydrophosphorylation Of Ynamidesmentioning
confidence: 99%
“…In 2019, employing alkynes with various leaving groups, the Chang group demonstrated that propargylic compounds 67a could be also used as nucleophile partners in the presence of electrophilic P-species to generate allenylphosphine oxides 67b (Scheme 67). 114 In this protocol, diverse leaving groups such as OAc, OTs, OMs, OP(O)(OPh)2, and halides can be installed on the alkyne substrates to afford the allenylphosphine oxides. Both alkyl and aryl substituents on R 1 -position of the alkynes were tolerated to give the target products 67c, 67d with high yields of 87% and 74%, respectively.…”
Section: Scheme 65 Proposed Mechanism For Hydrophosphorylation Of Ynamidesmentioning
confidence: 99%
“…Thus, it is highly desirable to develop a general method for the aminophosphination of allenes and to provide a general method for the preparation of alkenylphosphines, which could be used as viable substrates in subsequent organic reactions. 16 As part of our development of an approach for the formation of C−P bonds, 17 we have, for the first time, disclosed a metal-free aminophosphination of allenes toward the structurally diverse alkenylphosphines via the bifunctionalization reaction of allenes concomitant with the formation of the C−N and C−P bonds. This metal-free strategy makes it easy and efficient to obtain complex alkenylphosphine-substituted N-heterocycles, which are of great significance in medical chemistry.…”
mentioning
confidence: 99%
“…Unfortunately, no phosphinative cyclization products were obtained. Inspired by Hirano and Miura’s result and our previous success, we carried out the aminophosphination using 2,6-lutidine and Tf 2 O. The reaction of 1a (0.2 mmol) with 2a (0.4 mmol) in the presence of 2,6-lutidine (0.4 mmol) and Tf 2 O (0.4 mmol) was investigated in 1,2-dichloroethane (2 mL) for 2 h at room temperature.…”
mentioning
confidence: 99%